Olfactomedin 4 (OLFM4) expression is associated with nodal metastases in esophageal adenocarcinoma. - Lucia Suzuki; Fiebo J C Ten Kate; Annieke W Gotink; Hans Stoop; Michail Doukas; Daan Nieboer; Manon C W Spaander; Jan J B van Lanschot; Bas P L van Wijnhoven; Arjun D Koch; Marco J Bruno; Leendert H J Looijenga; et al. (PLoS ONE, 2019)
To date no informative biomarkers exist to accurately predict presence of lymph node metastases (LNM) in esophageal adenocarcinoma (EAC). We studied the discriminative value of Olfactomedin 4 (OLFM4), an intestinal stem cell marker, in EAC. Patients who had undergone esophagectomy as single treatment modality for both advanced (pT2-4) and early (pT1b) adenocarcinoma of the esophagus or gastro-esophageal junction were selected for this study from an institutional database (Erasmus MC University Medical Center, Rotterdam, The Netherlands). Surgical resection specimens of 196 advanced and 44 early EAC were examined. OLFM4 expression was studied by immunohistochemistry and categorized as low (<30%) or high (> = 30%) expression. Low OLFM4 was associated with poor differentiation grade in both advanced (60% vs. 34.8%, p = 0.001) and early EAC (39.1% vs. 9.5%, p = 0.023). LNM were present in 161 (82.1%) of advanced and 9 (20.5%) of early EAC respectively. Low OLFM4 was independently associated with the presence of LNM in advanced EAC in multivariable analysis (OR 2.7; 95% CI, 1.16-6.41; p = 0.022), but not in early EAC (OR 2.1; 95% CI, 0.46-9.84; p = 0.338). However, the difference in association with LNM between advanced (OR 2.7; 95% CI, 1.18-6.34; p = 0.019) and early (OR 2.3; 95% CI, 0.47-11.13; p = 0.302) EAC was non-significant (p = 0.844), suggesting that the lack of significance in early EAC is due to the small number of patients in this group. OLFM4 was not of significance for the disease free and overall survival. Overall, low expression of intestinal stem cell marker OLFM4 was associated with the presence of LNM. Our study suggests that OLFM4 could be an informative marker with the potential to improve preoperative assessment in patients with EAC. Further studies are needed to confirm the value of OLFM4 as a biomarker for LNM.